Analysis of Maximum Expiratory Flow Volume Curves Using Canonical Correlation Analysis - van Pelt, W.; Quanjer, Ph. H.; Wise, M. E.; van der Burg, E.; van der Lende, R. (Methods of Information in Medicine, 1985)
As part of a population study on chronic lung disease in the Netherlands, an investigation is made of the relationship of both age and sex with indices describing the maximum expiratory flow-volume (MEFV) curve. To determine the relationship, non-linear canonical correlation was used as realized in the computer program CANALS, a combination of ordinary canonical correlation analysis (CCA) and non-linear transformations of the variables. This method enhances the generality of the relationship to be found and has the advantage of showing the relative importance of categories or ranges within a variable with respect to that relationship. The above is exemplified by describing the relationship of age and sex with variables concerning respiratory symptoms and smoking habits. The analysis of age and sex with MEFV curve indices shows that non-linear canonical correlation analysis is an efficient tool in analysing size and shape of the MEFV curve and can be used to derive parameters concerning the whole curve.
Keywords: MEFV Curve; Curve Analysis; Canonical Correlation Analysis; Non-linear Transformations